Effect of memory CD4+ T cells’ signal transducer and activator of transcription (STATs) functional shift on cytokine-releasing properties in asthma - Chen, Zhihong; Pan, Jue; Jia, Yi; Li, Dandan; Min, Zhihui; Su, Xiaoqiong; Yuan, Honglei; Shen, Geng; Cao, Shengxuan; Zhu, Lei; Wang, Xiangdong (Cell biology and toxicology, 2017)
Background Recent data have demonstrated that long-lived memory T cells are present in the human lung and can play significant roles in the pathogenesis of specific allergic and autoimmune diseases. However, most evidence has been obtained from mouse studies, and the potential roles of memory T cells in human allergic diseases, such as asthma, remain largely unknown. Methods Thirty-three asthmatics, 26 chronic obstructive pulmonary disease (COPD) patients, and 22 healthy volunteers were enrolled in this study. Peripheral blood mononuclear cells (PBMCs) were isolated from the peripheral blood, and cell surface staining (CD4, CD45RO, CRTH2, CD62L, and CCR7) was performed for the detection of memory CD4 + T cells in blood. After stimulation with interleukin-27 (IL-27) or IL-4 for 15 min, the STAT1/STAT6 phosphorylation of memory CD4 + T cells was measured separately by flow cytometric techniques. The cytokine-releasing profiles after 6 days of culture under neutralization, T H 2, T H 2 + lipopolysaccharide (LPS), and T H 2 + house dust mite (HDM) conditions were detected by intracellular protein (IL-5, IL-17, and interferon (IFN)-γ) staining. Correlation analyses between the profile of memory CD4 + T cells and clinical characteristics of asthma were performed. Results The number of circulating memory CD4 + T (CD4 + Tm) cells in asthmatics was increased compared with that in the healthy subjects (48 ± 5.7 % vs. 32 ± 4.1 %, p < 0.05). Compared with COPD and healthy subjects, the phosphorylation of signal transducer and activator of transcription 1 (STAT1-py) was impaired in asthmatics, whereas the phosphorylation of signal transducer and activator of transcription 6 (STAT6-py) was slightly enhanced. This imbalance of STAT1-py/STAT6-py was attributed to T H 2 memory cells but not non-T H 2 memory cells in blood. The cytokine-releasing profiles of asthmatics was unique, specifically IL-5 high , IL-17 high , and IFN-r low , compared with those of COPD patients and healthy subjects. The IL-17 production levels in CD4 + Tm cells are associated with disease severity and positively correlated with medication consumption in asthma. Conclusions The long-lived, antigen-specific memory CD4 + T cells, rather than PBMCs or peripheral lymphocytes, might be the ideal T cell subset candidates for analyzing the endotype of asthma. Memory CD4 + T cells exhibiting a shift in STAT phosphorylation and specific cytokine-releasing profiles have the potential to facilitate the understanding of disease heterogeneity and severity, allowing the more personalized treatment of patients.